Agile Performance Improvement The New Synergy of Agile and Human Performance Technology - Winter, Robert (Apress : Imprint: Apress, 2015)
"1+1=3. That is the equation that summarizes the theme of this book. The book's message is to integrate the developmental principles of Agile with the result-focused approaches integral to performance consulting. Your outcomes in shaping human performance will be significant--and greater than if you only used one of these models. This is a book for anyone who seeks to work collaboratively with leaders to bring about continuously improving and sustainable organizational change." --Dana Gaines Robinson, coauthor of Performance Consulting Agile Performance Improvement demonstrates the mutual benefits that accrue to the worlds of performance consulting and agile software development when the values and principles of both are blended synergistically under the guidance of practitioners skilled in both. The agile performance improvement model blends the principles of human performance technology with the frameworks and practices of Agile. The result is an approach that maximizes the value of interactions among the consultant, the work team, and the customer. Unlike traditional end-to-end waterfall processes, agile performance improvement delivers value continuously and in small increments, relentlessly focusing on outcomes of value to the customer. Building on structures of Agile that are used in software development, such as Scrum, the agile performance improvement model considers the human component of holistic solutions in establishing a continuous stream of value. Bob Winter, a performance consultant, was the product owner for the corporate education scrum supporting an agile transition initiative for hundreds of engineering teams. From this cross-disciplinary experience, he discovered that the two cultures, two languages, and two methodologies of performance consulting and agile software development are-far from being incongruent, incompatible, or irrelevant to each other-in fact ideally suited to complement and support each other. Being agile improves the effectiveness of the performance consultant, and applying the lessons of human performance technology improves the effectiveness of software development teams. In Agile Performance Improvement, Winter teaches performance consultants how to apply agile principles, values, and methods usefully to the tasks of optimizing human performance in areas of practice not only adjoining but also well beyond the realm of software and IT engineering, such as corporate learning solutions, human resources systems, and non-software products. Conversely, he shows engineering teams immersed in an agile environment how to boost their performance using the principles and techniques taught and cultivated by performance consultants. The author, who has worked extensively on both sides of the traditional divide, recounts entertainingly but informatively how both sparks and fur can fly when geeks encounter people people.